Piceatannol bolsteres fetal haemoglobin formation in K562 cells via p38 map kinase activation and ERK inactivation - AAYUSH KUKREJA; RAKESH ARYA; ARCHANA TIWARI (Journal of BioScience and Biotechnology, 2015)
Elevation of the level of fetal haemoglobin (HbF) by pharmacological agents is a safe and a promising approach for treating beta thalassemia. In this study, the effect of piceatannol was studied in human erythroleukemic K562 cells for their role in gamma-globin mRNA and HbF induction. The role of p38 mitogen activated protein kinase (MAPK) and extracellular regulated protein kinase (ERK) signaling pathways were also examined. It was found that piceatannol significantly increased gamma-globin mRNA and HbF levels in dose and time dependent manner in K562 cells. This was determined by enzyme linked immunosorbent assay (ELISA) and western blot analysis. Pretreatment with p38 MAPK inhibitor (SB203580) obstructed the stimulatory effect of piceatannol in total and HbF activation. In contrast, no change in HbF level was observed in K562 cells when treated with ERK inhibitor (PD98059). Moreover, piceatannol activated p38 MAPK and inhibited ERK signaling pathways in K562 cells as shown by western blot analysis. Besides, the inhibitor SB203580 inhibited p38 MAPK activation when cells were pre-treated with piceatannol. In summary, piceatannol was found to be a strong inducer of HbF production in K562 cells. The results mark the role of p38 MAPK and ERK signaling as molecular targets for stimulation of HbF synthesis upon treatment with piceatannol.